Rapid detection of Heterobasidion annosum using a loop-mediated isothermal amplification assay - Hong-min, Zhou; Jian, Yu; Ying, Liu; Yuan, Yuan; Cui-ping, Wu; Yu-cheng, Dai; Jia-jia, Chen (Frontiers in Cellular and Infection Microbiology, 2023)
Heterobasidion annosum is one of the most aggressive pathogens of Pinus in Europe, causing considerable economic losses. To detect H. annosum for disease diagnosis and control, we developed a loop-mediated isothermal amplification (LAMP) reaction with a primer set designed from the glyceraldehyde 3-phosphate dehydrogenase (GAPDH) DNA sequences of H. annosum. The LAMP assay can efficiently amplify the target gene with 63℃ for 60 min in our study. In specificity tests, H. annosum was positively detected, and other 14 strains of Heterobasidion and 25 other fungi strains were negative. The detection limit of this assay is 100 pg·μL-1, and the assay was also successfully tested on woods and spore suspensions. This study provides a rapid method for diagnosing root and butt rot caused by H. annosum and surveillances in the ports of logs imported from Europe.